Anticipating socio-technical tipping points - Mey, Franziska; Mangalagiu, Diana; Lilliestam, Johan (Global Environmental Change-Human and Policy Dimensions, 2024)
The tipping point concept, widely recognized within the natural sciences, is experiencing a resurgence in social studies. The emerging field sees growing insights about characteristics and mechanisms of social system tipping; however, much disagreement remains. This includes whether social tipping points can be anticipated – determining its political relevance, as anticipation is essential for actions to intentionally trigger tipping. We address this disagreement and propose a framework which operationalises socio-technical tipping across subsystems and elements to anticipate tipping points, illustrated in two case comparisons. We show that whereas the transition to electric cars in Germany has started but is not about to tip, especially not regarding normative and regulatory regime factors, the same transition in Norway is about to tip, but still requires international car markets to tip before the sectoral transition is tipped and complete. Similarly, we show that the transition to a PV-based renewable power system in Germany has progressed strongly, both regarding technology and regime factors, but the system has not yet tipped: further efforts reforming infrastructure and regulation are essential. Hence, our findings emphasise the notion that while technological progress holds significance, it represents only one facet among several that must align for a system to undergo a tipping point.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Anticipating tipping; Socio-technical systems; Socio-technical tipping points; Systemic change